2017
DOI: 10.1021/acs.orglett.7b03113
|View full text |Cite
|
Sign up to set email alerts
|

Amycolamycins A and B, Two Enediyne-Derived Compounds from a Locust-Associated Actinomycete

Abstract: Two novel enediyne-derived natural products, amycolamycins A and B (1 and 2), were characterized from a locust-associated actinomycete Amycolatopsis sp. HCa4. Amycolamycins A and B contain a unique 2-(cyclopenta[a]inden-5-yl)oxirane core with suspected enediyne polyketide biosynthetic origin. Sequencing and analysis of the acm biosynthetic gene cluster allowed us to propose the biosynthetic pathway of 1 and 2. Moreover, amycolamycin A (1) was selectively cytotoxic to the M231 breast cancer cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…With ow cytometry and Western blot analysis, it was demonstrated that amycolamycin A suppressed the proliferation of M231 cells through inducing apoptosis through the activation of caspase-3. 10 Li et al isolated two new abscisic acid-type sesquiterpenes (11)(12) and one new ansamycin (13), together with four known ansamycins from Amycolatopsis alba DSM 44262. However, all of these examples showed no evident bacterial inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…With ow cytometry and Western blot analysis, it was demonstrated that amycolamycin A suppressed the proliferation of M231 cells through inducing apoptosis through the activation of caspase-3. 10 Li et al isolated two new abscisic acid-type sesquiterpenes (11)(12) and one new ansamycin (13), together with four known ansamycins from Amycolatopsis alba DSM 44262. However, all of these examples showed no evident bacterial inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…The genome of strain ncl2 T , unlike that of N. vaccinii NBRC 15922 T , contains presumptive NP-BGCs associated with the synthesis of amycolamycin A and B (2% gene similarity), type I polyketides that are cytotoxic for breast cancer cell lines [ 79 ], pepticinnamin E (6% gene similarity) which has the potential to treat cancer and malaria [ 80 ] and echosides A, B, C, D and E (11% gene similarity) and stambomycin A to D (36% gene similarity),which are antitumor antibiotics [ 81 ]. Strain ncl2 T also contains bioclusters predicted to encode for the antitubercular polyketides atratumycin (7% gene similarity) and capreomycin A and B (6% gene similarity), which are produced by ‘ Streptomyces aratus’ and ‘ Streptomyces capreolus’, respectively [ 32 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Amycolatopsis sp. HCa4 isolated from the gut of locusts (Locusta migratoria) produces amycolamycin A which is selectively cytotoxic to the M231 breast cancer cell line [204] and rifamorpholines A-E [13]. Rifamorpholines represent the new subclass of rifamycin antibiotics with an unprecedented 5/6/6/6 fused tetracyclic ring system and an unusually modified polyketide chain.…”
Section: Antibiotics Produced By Amycolatopsis Isolated From Poorly Studied Ecological Habitatsmentioning
confidence: 99%